Exploring the economic geography of Ireland - Edgar Morgenroth (The Economic and Social Research Institute (ESRI), 2008)
Only a few research papers have analysed the spatial distribution of economic activity in Ireland. There are a number of reasons for this, not least the fact that comprehensive data on the location of economic activity by sector across all sectors has not been available at the highly disaggregated spatial level. This paper firstly establishes the geographic distribution of employment at the 2 digit NACE level, using a novel approach that utilises a special tabulation from the CSO 2006 Census of Population Place of Work Anonymised Records (POWCAR). It then analyses the spatial patterns of this distribution using maps and more formal methods such measures of spatial concentration and tests for spatial autocorrelation. The paper considers the locational preferences of individual sectors, the degree to which specific sectors agglomerate and co-agglomerate, and thus will uncover urbanisation effects and differences across urban and rural areas regarding economic activity.
Keywords: R12; R14; R30; 330; economic geography; employment distribution; Wirtschaftsgeographie; Regionales Wachstum; Regionaler Arbeitsmarkt; Irland